Mechanisms of DBS: from informational lesions to circuit modulation and implications in OCD - Shea, Julia M.; Feigen, Chaim M.; Eskandar, Emad N.; Killian, Nathaniel J. (Frontiers in Human Neuroscience, 2025)
In 2009, treatment-resistant obsessive compulsive disorder (OCD) was approved as an indication for deep brain stimulation (DBS) under a Humanitarian Device Exemption (HDE). This review examines the mechanisms by which DBS produces its effects, focusing on its interaction with the pathophysiology of OCD, a condition thought to involve overactive cortico-striatal-thalamo-cortical (CSTC) circuits. We first review initial theories of excitation and inhibition. We then transition to discussion of the “informational lesion” hypothesis, which suggests that DBS may prevent the transmission of normative neural activity through the stimulated region. Specifically, high-frequency stimulation may disrupt pathological network patterns by masking or antidromically blocking synaptic inputs. Another hypothesis suggests that DBS disrupts network activity by driving action potentials antidromically, which activates upstream inhibitory interneurons and imposes rhythmic activity on local regions based on DBS stimulation parameters. Recent animal studies support these theories of disruption of pathological network activity, showing that high-frequency DBS can prevent neurons from responding to intrinsic oscillations, and thereby relieve OCD symptoms. This review also discusses the variable effects of DBS, noting immediate improvements in mood and anxiety, with with a more gradual reduction in OCD symptoms. These differential findings suggest that DBS may produce its effects through both immediate neuromodulation as well as long-term synaptic remodeling. In summary, this review synthesizes the current mechanistic understanding of DBS, focusing on OCD, and highlights areas of discrepancy between studies and opportunities for future research. A deeper mechanistic understanding of DBS could lead to more optimized and effective treatment, improving outcomes for patients with treatment-refractory OCD as well as other psychiatric conditions.